The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1093/molehr/5.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor expression in the human placenta

Abstract: The presence of progesterone receptors (PR) in the human placenta has been demonstrated using the reverse transcriptase-polymerase chain reaction technique. It was observed that the amount of PR in the human placenta is less during late gestation. Electrophoretic mobility shift assays with nuclear extract isolated from the first trimester and term placenta revealed three complexes when incubated with [ 32 P]dCTP-labelled progesterone response element, and, in competition with unlabelled progesterone response e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…6A), which is consistent with the human data of a previous study in which PR expression (both protein and mRNA) was shown to be much higher in first-trimester human placenta than in term placenta (31). The mechanisms by which the expression of nuclear receptors is regulated by pregnancy are not known but may be related to pregnancyspecific hormones, since some of these nuclear receptors such as AhR and HIF1␣ have already been shown to be regulated by pregnancy-specific hormones such as progesterone and 17␤-estradiol (4,10,31). When compared with Bcrp1 expression, we found significant correlations of Bcrp1 mRNA with HIF1␣, AhR, and ER␤ mRNA in placenta, with HIF1␣ mRNA in kidney, and with AhR and ER␣ mRNA in liver (Table 1 and Fig.…”
Section: Discussionsupporting
confidence: 92%
“…6A), which is consistent with the human data of a previous study in which PR expression (both protein and mRNA) was shown to be much higher in first-trimester human placenta than in term placenta (31). The mechanisms by which the expression of nuclear receptors is regulated by pregnancy are not known but may be related to pregnancyspecific hormones, since some of these nuclear receptors such as AhR and HIF1␣ have already been shown to be regulated by pregnancy-specific hormones such as progesterone and 17␤-estradiol (4,10,31). When compared with Bcrp1 expression, we found significant correlations of Bcrp1 mRNA with HIF1␣, AhR, and ER␤ mRNA in placenta, with HIF1␣ mRNA in kidney, and with AhR and ER␣ mRNA in liver (Table 1 and Fig.…”
Section: Discussionsupporting
confidence: 92%
“…However, there is some controversy as to whether the PR is expressed in placental trophoblasts. Several studies have not been able to detect PR in the placenta [18,27,28], whereas a number of other studies have [19,20]. PR exists in human as two proteins, PR-A and PR-B, encoded by a single gene.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Karalis et al [18] concluded that P4 downregulation of CRH gene expression in placenta occurred through the glucocorticoid receptor (GR) because they did not detect P4 receptor (PR) expression in placental cells. However, several studies have shown that the PR is expressed by placental cells [19,20]. Thus the mechanisms by which P4 could inhibit placental CRH production are unclear.…”
mentioning
confidence: 99%
“…They also show that these increases in uptake can be attributed to increased NIS expression in the placental cultures upregulated in response to incubation with those hormones. The ability of pregnancy-related hormones to influence 125 I uptake and NIS expression is obviously dependent on the presence and abundance of individual hormone receptors in late pregnancy placentas [31,32,33,34]. …”
Section: Discussionmentioning
confidence: 99%